Energy Saving in Electromechanical Grain Cleaning Systems - Bazaluk, Oleg; Postnikova, Marina; Halko, Serhii; Галько, Сергій Віталійович; Kvitka, Serhii; Квітка, Сергій Олексійович; Mikhailov, Yevhen; Михайлов, Євген Володимирович; Kovalov, Oleksandr; Ковальов, Олександр Олександрович; Suprun, Olena; Супрун, Олена Миколаївна; et al. (My University, 2022)
The article is concerned with energy conservation in the process of cleaning grain. The study aimed to find ways of reducing energy consumption when cleaning food grains by using energy-saving operating modes (ESOM) on the production lines of grain storage facilities. For this purpose, experimental tests were performed which involved studying the effects of physical and chemical properties of grain as well as the influence of various operating modes of the production lines on the specific energy consumption (SEC), which was found to be the most informative indicator for determining ESOM. The mathematical description of the target function was carried out by conducting a multifactorial experiment with the application of the orthogonal central composite design (OCCD) of the second order. Calculations produced a number of mathematical models describing the dependence of the response function on the input parameters. The proposed approach made it possible to obtain the minimum SEC for cleaning food grains and to develop practical recommendations for ways to reduce energy consumption, which resulted in the development of scientifically based SEC standards for a grain cleaning machine.
Keywords: energy efficiency; energy saving; multifactorial experiment; grain cleaning machine